PERBANDINGAN HASIL BELAJAR IPA SISWA YANG DIAJAR DENGAN MODEL QUANTUM DAN YANG DIAJAR DENGAN MODEL PEMBELAJARAN KONVENSIONAL - Sudarto, Sudarto (Jurnal Cakrawala Ilmiah, 2022)
This research was an experiment study with a Randomized Control Group Only design which aimed to determine the comparison of Science learning outcomes of students taught using quantum model and student Science learning outcomes that were taught using conventional learning model. The population were all the grade 7th students of SMPN 33 Makassar. The sampling method is Simple Random Sampling. The research data was obtained by providing tests in the form of multiple-choice questions and essays. Data analysis techniques were by inferential analysis using an independent sample t-test. The results showed that tcount (7.16) > ttabel (1.67). Conclusion: the science learning outcomes of students taught with quantum learning model were better than the science learning outcomes of students taught with conventional models.